A STUDY OF LUXURY GOODS MARKET IN INDIA - Indorewalla, Anahita K. (2008)
Luxury goods and services have a niche market of their own that is placed at the top of the heap of society. This phenomenon has existed since historical times and is there in this age of globalization and technical innovation, coupled with growth in information and communication technology. The creation of a niche market for luxury goods is based upon strong aspirations of the consumers to attain certain levels in the society and get psychological and aesthetic satisfaction along with the expectation of getting high quality goods. This is true for existing and emerging markets for luxury goods including India. The analysis of literature and corresponding focused interviews related to this topic and its area of study i.e. India and its consumers of luxury goods vindicate the theories about consumer perception of luxury goods and the development of a corresponding market in India. The conclusion drawn with regards to luxury goods and the related growth of luxury goods market is that it is developing along expected lines in India and will develop in future. The recommendations of this study are: Observe the growth of future luxury market in India with regards to increase in membership of consumers in the exclusive group that buys luxury goods. Facilitate the improvement of luxury market both at the policy level and the market level so that it reaches the next stage of development in the luxury goods market in terms of spatial growth, variety and range of goods offered in the luxury goods market. Create conditions for development of indigenous base for luxury goods in India considering the future potential of this market